Implementing best purchasing and supply management practices : lessons from innovative commercial firms - Moore, Nancy Y., 1947-; Baldwin, Laura H., 1967-; Camm, Frank A., 1949-; Cook, Cynthia R., 1965-; Rand eBooks (Santa Monica, CA : RAND, 2002)
Because the U.S. Air Force spends over one-third of its budget on nonweapons purchased goods and services, such purchases are a prime target area in which to seek performance improvements and cost savings. Prompted by a need for improved performance from its supply base, the Air Force has become increasingly aware of the advantages of using market research, contract consolidation, supply base rationalization, and other leading purchasing and supply management (PSM) practices in its dealings with suppliers. To aid the Air Force in its PSM efforts, RAND examined how innovative commercial firms implement such practices in their purchases of goods and services. After a review of the academic and trade literature, the study team conducted a series of elite interviews using a structured questionnaire to gather primary data from "best in class" commercial firms. The key findings are that (1) innovative commercial firms are moving to a strategic, goal-oriented approach to PSM, (2) implementing new PSM practices can take a number of years and often requires significant, permanent change throughout the organization, and (3) the Air Force needs strategies to sustain continuity of support for serious PSM change from one leadership team to the next.
"RAND Project Air Force."
Includes bibliographical references (p. 185-201).
Also available on the internet via WWW in PDF format.
Description based on print version record.
Keywords: United States. -- Air Force -- Inventory control; United States. -- Air Force -- Procurement -- Evaluation; United States. -- Air Force -- Rules and practice -- Evaluation; United States. -- Air Force -- Supplies and stores; Business logistics; Inventory control; Purchasing -- Management; Electronic books